Análise do uso dos anglicismos crush, ship, stalker e match no Português Brasileiro - REIS, Elaine Gomes da Silva (2022)
This research was motivated by the interest in observing how words in English behave in linguistic and cultural terms, having as a starting point their uses in the virtual environment. The investigation begins with Instagram posts, an option that stems from the finding that Brazilian users of this social network adopt a considerable number of Anglicisms due to the influence of sociocultural factors. Throughout the research, occurrences within and outside the Internet of the researched Anglicisms were analyzed. Therefore, this research had as its object of investigation English words into Brazilian Portuguese (BP), from the perspective of Cultural Semantics (SC), which is characterized as a “[...] the meanings attributed to words or other expressions of a language and the culture in which that same language is inserted” (FERRAREZI, 2013, p. 71). Based on this concept, we understand that this current of research on Semantics tries to explain the meanings and observe the importance of cultural aspects for the construction of linguistic utterances. We intend to understand the relationship between the meanings attributed to Anglicisms and our culture, since, for Cultural Semantics, a language must represent a world and its events. One of the great advances in the area in recent years has been to demonstrate that the structures of natural languages are also reflections of culture, social organizations and the environment, thus making evident the importance of the living part of the language, that is, the language in use. Furthermore, we seek theoretical basis in the readings carried out in Alves (2002), Barbosa (2009), Carvalho (2009) and other authors that deal with Anglicisms and neologisms. And, finally, authors such as Rajagopalan (2003), Crystal (2005) and Kumaravadivelu (2006) on Globalization and Internet studies. The present work has, therefore, the general objective of analyzing the use of the anglicisms crush, ship, stalker and match in Brazilian Portuguese. Furthermore, we specifically aim to observe the use of selected Anglicisms in Instagram posts, as well as their occurrences in contexts inside and outside the online environment. We also aim to understand the semantic-cultural domains of the selected Anglicisms in the light of Cultural Semantics and to verify the existence of correspondents in Brazilian Portuguese lexicon for the Anglicisms researched.